2022
DOI: 10.1039/d2ra00300g
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and photocatalytic studies of hexagonal boron nitride nanotubes: a potential candidate for wastewater and air treatment

Abstract: Photocatalytic degradation studies of methyl orange using BNNTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…In addition, future studies in the same field can help in building an alternative experimental setup, where the material’s absorption, their effects, and the interactions between the various particles can be studied ( Maaza et al, 2006 ; Mtshali et al, 2013 ). Thus, the radiation shielding properties of nanomaterials will be best known with the additional studies to be done ( Izerrouken et al, 2011 ; Ahmad et al, 2022 ; Khalid et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, future studies in the same field can help in building an alternative experimental setup, where the material’s absorption, their effects, and the interactions between the various particles can be studied ( Maaza et al, 2006 ; Mtshali et al, 2013 ). Thus, the radiation shielding properties of nanomaterials will be best known with the additional studies to be done ( Izerrouken et al, 2011 ; Ahmad et al, 2022 ; Khalid et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Chemical dye, organic and mineral materials, and synthetic dye all come from industrial, urban, and agricultural resources, with chemical dye being the maximum harmful pollutant emanating from fabric industries [1][2][3]. Many industries use water treatment plants to eliminate pollution from wastewater at a small price for environmental benefits [4][5][6]. is helps to improve and conserve the quality of water for drinking and other purposes.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the current study, hBN nanoparticles were embedded directly inside the glass matrix, and following the degradation of the glass in the cell culture medium, 2D nanoparticles may diffuse into the cell membrane more easily. Similarly, a recent study by Khalid et al [ 54 ] reported the toxicological effects of boron nitride nanotubes. Results showed that the cytotoxicity of boron nitride nanotubes was higher in HeLa cancer cells (80%) compared to the HEK-293 normal cells (60%) for 48 h incubation.…”
Section: Resultsmentioning
confidence: 83%